P473 Corticosteroid-free clinical remission rates with guselkumab maintenance therapy in patients with moderately to severely active Crohn's disease: Week 48 analyses from the phase 2 GALAXI 1 study. (30th January 2023) - D'Haens, G; Afzali, A; Filip, R; Rolim, A; Terry, N A; Salese, L; Sahoo, A; Frustaci, M E; Yang, Z; Andrews, J M; Danese, S; Hisamatsu, T
Abstract: Background: Corticosteroids are often used in Crohn's disease (CD) to control inflammation. However, they are associated with adverse events; thus, achieving and maintaining remission without corticosteroids is a major treatment goal. GALAXI 1, a phase 2b, double-blind, placebo (PBO)-controlled study, evaluated efficacy and safety of guselkumab (GUS), a selective interleukin-23p19 subunit antagonist, in patients (pts) with moderately to severely active CD. Primary efficacy and safety data were presented previously. Here, we report corticosteroid-free clinical remission rates through Week (Wk) 48. Methods: Pts with moderately to severely active CD were randomised in a treat-through design to GUS 200, 600, 1200mg; ustekinumab (UST) ~6mg/kg; or PBO intravenous (IV) induction followed by maintenance dosing (GUS 200mg IV-->GUS 100mg subcutaneous [SC] every 8 weeks [q8w], GUS 600mg IV-->GUS 200mg SC q4w, GUS 1200mg IV-->GUS 200mg SC q4w, UST ~6mg/kg IV-->UST 90mg SC q8w, PBO nonresponders-->UST ~6mg/kg IV-->UST 90mg SC q8w, PBO responders-->PBO SC q4w). Corticosteroid tapering was mandatory from Wk12 if medically feasible. Efficacy endpoints included corticosteroid-free CD Activity Index (CDAI) clinical remission (<150) and pt-reported outcome (PRO)-2 remission at Wk48 in the primary efficacy population. Pts randomised to PBO were not included in Wk48 efficacy analyses. GALAXI 1 was not powered to evaluate efficacy differences between treatment groups at Wk48; UST was a reference arm. Analyses were prespecified but not multiplicity controlled. Results: At Wk48, 55.7-71.4% of pts in the GUS dose groups achieved corticosteroid-free CDAI clinical remission (Table 1). Similar rates were observed when the corticosteroid-free duration was ≥30 or ≥90 days before Wk48. Among pooled pts in CDAI clinical remission at Wk48 in the GUS groups, 115/120 (95.8%) were corticosteroid free. At Wk48, 49.2-68.3% of pts in the GUS dose groups achieved corticosteroid-free PRO-2 remission (Table 1). Among pooled pts in PRO-2 remission at Wk48 in the GUS groups, 105/110 (95.5%) were corticosteroid free. Outcomes in the reference UST group are shown in Table 1. Among pts in the GUS dose groups, 30.2-39.3% were using corticosteroids at Wk0 (median prednisone equivalent dose 20.0mg/d in each group); at Wk48, 60.0-78.9% of these pts met corticosteroid-free criteria (Table 2). Conclusion: High rates of corticosteroid-free CDAI clinical and PRO-2 remission were achieved at Wk48 in the GUS dose groups. Among pts in clinical remission, most were corticosteroid free. Nearly all pts maintained corticosteroid-free CDAI clinical remission for ≥90 days. GUS IV induction followed by SC maintenance therapy also effectively reduced corticosteroid use at Wk48.